PENGEMBANGAN WEB PROGRAM LATIHAN BERBASIS DIGITAL - Kusuma, I Dewa Made Aryananda Wijaya; Pramono, Bayu Agung; Siantoro, Gigih; Bulqini, Arif; Yuhantini, Eva Ferdita; Prianto, David Agus (Journal of Sport and Exercise Science, 2022)
The research aims to develop a digital application for preparing an exercise program to make it easier for trainers to prepare an exercise program. This research uses Agile Development Methods. This research was conducted at the Faculty of Sports Science, Unesa, involving a sample of 50 students. The sampling technique in this study used a purpose random sampling technique. Data collection techniques using surveys. Based on the results of observations made to the sample, a total of 78% of the sample stated that the development of this application was going very well, 14% was good and 8% was sufficient. It can be concluded that this digital-based training program web is suitable for use by trainers in preparing training programs.